On the Influence of Pressure, Phase Transitions, and Water on Large‐Scale Seismic Anisotropy Underneath a Subduction Zone - John Keith Magali; Christine Thomas; Estelle Elisa Ledoux; Yann Capdeville; Sébastien Merkel (Geochemistry, Geophysics, Geosystems)
Abstract Seismic anisotropy mainly originates from the crystallographic preferred orientation (CPO) of minerals deformed in the convective mantle flow. While fabric transitions have been previously observed in experiments, their influence on large‐scale anisotropy is not well‐documented. Here, we implement 2D geodynamic models of intra‐oceanic subduction coupled with mantle fabric modeling to investigate the combined effect of pressure (P)‐and water‐dependent microscopic flow properties of upper mantle and upper transition zone (UTZ) minerals, respectively, on large‐scale anisotropy. We then compare our anisotropy models with anisotropic tomography observations across the Honshu subduction zone. Our results for the upper mantle correlate well with observations, implying that the P‐dependence of olivine fabrics is sufficient to explain the variability of anisotropy. Meanwhile, a dry UTZ tends to be near‐isotropic whereas a relatively wet UTZ could produce up to 1% azimuthal and ∼2% radial anisotropy. Because water facilitates CPO development, it is therefore likely a requirement to explain the presence of anisotropy in the transition zone close to subducting slabs.